2002
DOI: 10.1191/0748233702th153oa
|View full text |Cite
|
Sign up to set email alerts
|

‘Death... more desirable than life’? The human skeletal record and toxicological implications of ancient copper mining and smelting in Wadi Faynan, southwestern Jordan

Abstract: Skeletal material from 36 people, dating from the early Christian era, who lived by or worked in the notorious Roman copper mines of Phaeno, were analysed to determine their exposure to copper and lead. We demonstrate that many of the bones analysed had a substantially higher concentration of these cations than modern individuals exposed to metals through industrial processes. Health, toxicological and environmental implications of these data are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
1
26
0
2
Order By: Relevance
“…Under certain conditions, heavy metals released by lead/zinc mining may activate, migrate and accumulate in various target media that may directly or indirectly impact plants, animals and humans (Wang et al 1994;Chiaradia et al 1997;Grattan et al 2002;Liu et al 2005a, b;Pusapukdepob et al 2009;Bai and Yan 2008;Kim et al 2008). Lead is not an essential element for the human body, and excessive intake can damage the nervous, skeletal, circulatory, enzymatic, endocrine, and immune systems.…”
Section: Introductionmentioning
confidence: 96%
“…Under certain conditions, heavy metals released by lead/zinc mining may activate, migrate and accumulate in various target media that may directly or indirectly impact plants, animals and humans (Wang et al 1994;Chiaradia et al 1997;Grattan et al 2002;Liu et al 2005a, b;Pusapukdepob et al 2009;Bai and Yan 2008;Kim et al 2008). Lead is not an essential element for the human body, and excessive intake can damage the nervous, skeletal, circulatory, enzymatic, endocrine, and immune systems.…”
Section: Introductionmentioning
confidence: 96%
“…Gonzá lez-Remíers et al (2001, 2003 reported copper and lead data obtained from a geographically remote and uncontaminated ancient human population of the Canary Islands. Grattan et al (2002Grattan et al ( , 2005 and Pyatt et al (2005) highlighted the correlation between copper and lead concentrations in bones and the degree of environmental pollution as a result of the development of the mining industry and metalliferous processing in one of the metallurgical centers of the ancient world, the Wadi Faynan. Drasch (1982) and Nriagu et al (cited in Grattan et al, 2002) emphasize the lead uptake originating from the utensils used in the Roman populations.…”
Section: Introductionmentioning
confidence: 98%
“…No obstante, dicha función, también favorece la bioacumulación de algunos metales derivados de la polución (Arnay-De-LaRosa et al, 1998;Baranowska et al, 1995;González-Reimers et al, 2003;Grattan et al, 2002;Martínez-García et al, 2005), motivo por el cual los huesos subfósiles pueden utilizarse como un método indirecto de medida de la contaminación ambiental en la antigüedad, al menos desde los orígenes de la metalurgia durante la prehistoria reciente (Nocete, 2006). Por ejemplo, en el sur de la Península Ibérica se han detectado niveles elevados de Cu, Zn, Pb y As en muestras de suelo y bivalvos datados en la Edad del Cobre (Aléx et al, 2004;Nocete et al, 2005), pero no se han realizado análisis en restos óseos.…”
Section: Introductionunclassified